A history of safeguarding disabled children from 1840 to 1960 in the Republic of Ireland - Flynn, Susan (My University, 2025)
This article provides a history of safeguarding of disabled children between 1840 and 1960 in the Republic of Ireland. Therein, safeguarding involves direct and indirect measures undertaken to promote the safety and welfare of disabled children in need of protection. Two distinct subphases of history are addressed. The first is a period characterised by informal familial care versus segregated institutional care. Within this, institutional care operated under medical, religious and philanthropic discourses and auspices. The second is a historical period when newfound State intervention toward inclusion and progression was evident. This period saw institutionalisation reach its most staggering peaks, only to sharply decline in the wake of revelations about widespread institutional care. The article focuses on key changes, across these phases, to child protection and welfare policy and practice in Ireland for disabled children. The central argument is that the Church, the State and the immediate family have had varying roles in safeguarding disabled children, in the context of a lack of evidence of any significant community and societal involvement. This argument is substantiated by and emergent from accounts of history. To elaborate upon the sustaining reasons for this proposition, an affirmative model of disability is applied in discussion, to theoretically consolidate learning from the past. In concluding, the article emphasises the importance of history as a rich source of wisdom for future excellence in policy and practice.
PUBLISHED
https://doi.org/10.1016/j.childyouth.2025.108280
Keywords: history, child protection and welfare, disability, children, Ireland